Perceptions of personal security in social media and search engines: A realistic reflection of actual crime rates? - Johannes Rieckmann; Jan-Lucas Schanze (DIW Economic Bulletin, 2015)
The most common method of measuring subjective fear of crime in the general population has traditionally been through surveys. With the spread of digital technologies, however, data from social media and search engines could now help researchers learn more about people's subjective perceptions of certain types of crime. The present article will show that although the analysis of data from social media and search engines is not suitable as an indicator of actual crime levels in Germany, it can certainly be a cost-effective supplement to traditional methods of collecting data on perceived crime levels.
Keywords: H79; K42; R12; Z18; 330; crime; crime statistics; indicator; perception; security; social media; social network; search engine